Diagnostic and cost utility of whole exome sequencing in peripheral neuropathy. Issue 5 (26th April 2017) - Walsh, Maie; Bell, Katrina M.; Chong, Belinda; Creed, Emma; Brett, Gemma R.; Pope, Kate; Thorne, Natalie P.; Sadedin, Simon; Georgeson, Peter; Phelan, Dean G.; Day, Timothy; Taylor, Jessica A.; et al.
Abstract: Objective: To explore the diagnostic utility and cost effectiveness of whole exome sequencing (WES) in a cohort of individuals with peripheral neuropathy. Methods: Singleton WES was performed in individuals recruited though one pediatric and one adult tertiary center between February 2014 and December 2015. Initial analysis was restricted to a virtual panel of 55 genes associated with peripheral neuropathies. Patients with uninformative results underwent expanded analysis of the WES data. Data on the cost of prior investigations and assessments performed for diagnostic purposes in each patient was collected. Results: Fifty patients with a peripheral neuropathy were recruited (median age 18 years; range 2–68 years). The median time from initial presentation to study enrollment was 6 years 9 months (range 2 months–62 years), and the average cost of prior investigations and assessments for diagnostic purposes AU$4013 per patient. Eleven individuals received a diagnosis from the virtual panel. Eight individuals received a diagnosis following expanded analysis of the WES data, increasing the overall diagnostic yield to 38%. Two additional individuals were diagnosed with pathogenic copy number variants through SNP microarray. Conclusions: This study provides evidence that WES has a high diagnostic utility and is cost effective in patients with a peripheral neuropathy. Expanded analysis of WES data significantly improves the diagnostic yield in patients in whom a diagnosis is not found on the initial targeted analysis. This is primarily due to diagnosis of conditions caused by newly discovered genes and the resolution of complex and atypical phenotypes.